Cancer chemoprevention by cyclooxygenase 2 (COX-2) blockade: results of case control studies - Harris, Randall E; Beebe-Donk, Joanne; Alshafie, Galal A (Sub-cellular biochemistry, 2007)
Significant use of selective cyclooxygenase-2 (COX-2) blocking agents prescribed for the treatment of arthritis during 1999 to 2005 facilitates epidemiologic investigations to illuminate their chemopreventive effects against human cancer. We therefore conducted a set of case control studies of selective COX-2 blocking agents to determine their chemopreventive potential for the four major cancers: breast, prostate, colon, and lung. Newly diagnosed cases (323 breast cancer patients, 229 prostate cancer patients, 326 colon cancer patients, and 486 lung cancer patients) were ascertained during 2002 to September 30, 2004, at The James Cancer Hospital and Solove Research Institute, The Ohio State University Medical Center, Columbus, Ohio. All cases of invasive cancer were confirmed by examination of the pathology report. Healthy controls without cancer were ascertained from hospital screening clinics during the same time period. Controls were frequency matched at a rate of 2:1 to the cases by age, gender, and county of residence. We collected information on type, frequency, and duration of use of selective COX-2 inhibitors and nonselective nonsteroidal anti-inflammatory drugs (NSAIDs). Other potentially important risk factors (smoking, drinking, body mass, medical history, blood pressure and cholesterol medications, family history of cancer, occupational history, and reproductive history for women) were also recorded for each subject. Estimates of odds ratios were obtained with adjustment for age and other potential confounders using logistic regression analysis. Use of selective COX-2 inhibitors resulted in a significant risk reduction for each type of cancer (71% for breast cancer, 55% for prostate cancer, 70% for colon cancer, and 79% for lung cancer) and an overall 68% risk reduction for all four cancers. This investigation demonstrates that COX-2 blocking agents have strong potential for the chemoprevention of cancers of the breast, prostate, colon and lung.